Geophysical survey of Neovolcanic complexes in the first protection zone of the Sliač Spa and the Baková jama - PAŠIAKOVÁ, Mariana; GAJDOŠ, Vojtech; BUČOVÁ, Jana; DÉREROVÁ, Jana; STRAKA, Adam; HLAVŇOVÁ, Petra; BRIXOVÁ, Bibiana (Contributions to Geophysics and Geodesy, 2014)
The main purpose of the survey in the 1st protection zone area of the SliačSpa and the Bakov´a jama was to clarify the geological-tectonical structure. The verticalelectric sounding (VES) technique was selected as the main geophysical survey method.Additionally, the soil radon emanometry was carried out to verify tectonic lines’ presence.The outcrop of Pre-Tertiary basement was discovered in the form of small isolated island.No tectonic line was identified based on the evaluation of profile radon concentration.The results of geoelectrical measurements are presented in 8 geological-geophysical crosssections.The results and the tectonic lines’ courses interpreted by the VES method aredrawn in the map of new indications. The isoline maps and 3D model of Pre-Tertiarybasement were constructed.